2012
DOI: 10.1167/iovs.11-9345
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Proximal versus Distal Intraorbital Optic Nerve Diffusion Tensor Magnetic Resonance Imaging Properties in Glaucoma Patients

Abstract: Purpose. To analyze in vivo the diffusion tensor magnetic resonance imaging (DT-MRI) properties of the intraorbital optic nerve at two different levels: Proximal to the optic nerve head (ONH) and distal to the ONH at the level of the orbital apex in glaucoma patients. Methods. Twenty-four patients with primary open-angle glaucoma were examined. The categorization into early and severe glaucoma was performed by Hodapp's classification. Fifteen healthy individuals served as controls. DT-MRI was performed with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 27 publications
(49 reference statements)
3
45
0
Order By: Relevance
“…In our study, optic nerve-1 diffusion parameters were found to be more closely correlated with OCT and VF findings. This is also consistent with the recent study of Bolacchi et al in which, proximal optic nerve findings were found to be more closely correlated with OCT data in early stage glaucoma [26].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, optic nerve-1 diffusion parameters were found to be more closely correlated with OCT and VF findings. This is also consistent with the recent study of Bolacchi et al in which, proximal optic nerve findings were found to be more closely correlated with OCT data in early stage glaucoma [26].…”
Section: Discussionsupporting
confidence: 93%
“…For this purpose transversal views of the eye were acquired using a spatial resolution of (0.2 x 0.2 x 1.0) mm 3 ( Figure 8a) and of (0.3 x 0.3 x 1.0) mm 3 ( Figure 8b). We could also demonstrate the feasibility of inversion recovery prepared 3D GRE using a spatial resolution of (0.4 x 0.4 x 1.0 mm) 3 ( Figure 8c) and T2-weighted 2D FSE with a spatial resolution of (0.25 x 0.25 x 0.7 mm) 3 ( Figure 8d). For comparison, the T2-weighted 2D FSE protocol was performed using the 1TX24RX, 1TX1RX and 1TX32RX head coil configurations.…”
Section: In Vivo Feasibility Studymentioning
confidence: 84%
“…With a spatial resolution of (0.3 x 0.3 x 1.0) mm 3 we could clearly discern anatomical details of the eye including the anterior chamber, posterior chamber, lens nucleus, lens cortex, vitreous humor and orbital muscles (Figure 7a). Rather uniform signal intensity was observed across the eye as underlined by the signal intensity profiles through a sagittal view of the lens nucleus and the vitreous humor (Figure 7b).…”
Section: In Vivo Feasibility Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Glaucomatous optic neuropathy is characterized by a typical appearance of the optic nerve head, including a loss of neuroretinal rim, deepening of the optic cup, disc hemorrhages, parapapillary chorioretinal atrophy, decrease in the diameter of the retinal arterioles, and a diffuse and or local retinal nerve fiber layer loss (4). Formerly the definition of human glaucoma included elevation of IOP over the upper limit of the normal range (most frequently >21 mm Hg) (3).…”
Section: Discussionmentioning
confidence: 99%